이마에 발생한 석회화된 지방종 - 황소민; 김형도; 임광열; 정용휘; 송제니퍼김; Hwang, So Min; Kim, Hyung Do; Lim, Kwang Ryeol; Jung, Yong Hui; Song, Jennifer K (Archives of craniofacial surgery, 2012)
Purpose: Although lipoma is known as one of the most common soft tissue tumors, calcification in lipoma is very rare in its occurrence. This calcified lipoma has been reported by some as a result of regression of lipoma, but its genesis is not clearly known yet with various opinions being discussed regarding its possible metabolic relation to hypercalcemia or hyperphosphatemia to be considered as a regression phase of lipoma. The authors would like to present this unusual case of calcified lipoma. Methods: A 50-year-old male patient visited our hospital with complaint of an enlarging mass on his right forehead which has been acknowledged for 5 years' period. On physical examination, a mass was observed on his forehead as palpable, non-tender, mobile and firm in its consistency. Ultra sonogram examination revealed a well-demarcated mass (1.92 cm) with central echoic zone at deep layer of forehead. Mass excision and biopsy were performed subsequently. Results: According to the pathological report, the diagnosis confirmed the lipoma consisting of grown-up adipocyte and calcification. Neither growing lipoma nor relapse was observed for postoperative three years' follow-up of the patient. Conclusion: Now that the calcified lipoma was successfully removed and cured by a simple mass excision, authors hereby report the case of calcified lipoma on forehead.